Design of Encryption Algorithm in Combined Spatial and Frequency Domains for Telescope Grayscale and Bayer Images - KC, Ting; KH, Yeap; PC, Teh; KC, Lai; Francis-Lothai, Florence (Journal of Advanced Research in Signal Processing and Applications, 2022)
Digital images transmission has grown dramatically over the past years in various applications, for instance, transmission of telescope images. In this research, a novel encryption algorithm that combines both spatial and frequency domains is studied. Telescope images in grayscale and Bayer array are applied in our algorithm. Effectiveness of the proposed algorithm has been analyzed in terms of several key analyses, such as histogram distribution, Number of Pixel Changing Rate (NPCR), Unified Average Changing Intensity (UACI), Peak Signal to Noise Ratio (PSNR), Information Entropy and Structural Similarity Index (SSIM). Empirical results suggest that our proposed algorithm can be practically applied to encrypt both grayscale and Bayer telescope images. How to cite this article: Ting KC, Yeap KH, Teh PC et al. Design of Encryption Algorithm in Combined Spatial and Frequency Domains for Telescope Grayscale and Bayer Images. J Adv Res Sig Proc Appl 2021; 3(2): 1-5.